2017
DOI: 10.1007/s00774-017-0827-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale investigation on the effects of additional weight bearing in combination with low-magnitude high-frequency vibration on bone quality of growing female rats

Abstract: This study aimed to explore the effects of additional weight bearing in combination with low-magnitude high-frequency vibration (LMHFV; 45 Hz, 0.3 g) on bone quality. One hundred twenty rats were randomly divided into ten groups; namely, sedentary (SED), additional weight bearing in which the rat wears a backpack whose weight is x% of the body weight (WBx; x = 5, 12, 19, 26), basic vibration (V), and additional weight bearing in combination with LMHFV in which the rat wears a backpack whose weight is x% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 49 publications
0
14
0
2
Order By: Relevance
“…However, WBV was reported to improve bone mass and structure by increasing bone formation or decreasing bone resorption in both normal and osteopenia rodents older than 4 weeks [[13], [14], [15], [16], [17]]. On the other hand, the effects of WBV on bone properties were inconsistent among young rodents under the age of 4 weeks [18,19]. One study previously reported that femoral stiffness and yield load are significantly increased by 45-Hz WBV (0.3 g , 15 min/d, 5 d/wk) for 5 weeks in wild-type female mice compared with those of wild-type female mice without WBV [19].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, WBV was reported to improve bone mass and structure by increasing bone formation or decreasing bone resorption in both normal and osteopenia rodents older than 4 weeks [[13], [14], [15], [16], [17]]. On the other hand, the effects of WBV on bone properties were inconsistent among young rodents under the age of 4 weeks [18,19]. One study previously reported that femoral stiffness and yield load are significantly increased by 45-Hz WBV (0.3 g , 15 min/d, 5 d/wk) for 5 weeks in wild-type female mice compared with those of wild-type female mice without WBV [19].…”
Section: Discussionmentioning
confidence: 99%
“…One study previously reported that femoral stiffness and yield load are significantly increased by 45-Hz WBV (0.3 g , 15 min/d, 5 d/wk) for 5 weeks in wild-type female mice compared with those of wild-type female mice without WBV [19]. In contrast, another study previously reported that BMD and BV/TV of the femoral head and BMD of the femoral cortical bone are decreased by 45-Hz WBV (0.3 g , 15 min/d, 7 d/wk) for 12 weeks in 4-week-old normal female rats [18]. It should be noted that the WBV conditions excluding the intervention period and intervention days per week were the same in these 2 studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations